The Characteristics of Professional Administrator Affecting the Efficiency Teacher’s Performance in the School Under the Secondary Education Service Area Office Nonthabury - Porncharoong , Rattanaporn; Sangmookda , Suthasinee (Journal of Dhamma for Life, 2025)
The purposes of this research were: 1) to study the characteristics of professional administrator under the Secondary Educational Service Area Office Nonthaburi 2) to study the efficiency teacher’s performance in the schools under the Secondary Educational Service Area Office Nonthaburi and, 3) to study the characteristics of professional administrator affecting the efficiency teacher’s performance in the schools under the Secondary Educational Service Area Office Nonthaburi. The sample group in this research is 36 school administrators and 320 teachers, total of 356 informants. The instrument used in this study was questionnaires. The data was analyzed using package program. The statistics used in data analyzing were frequency, percentage, arithmetic mean, and standard deviation. The hypothesis test used the analysis stepwise multiple regression analysis. The results of this research were as follows: 1. The characteristics of professional administrator under the Secondary Educational Service Area Office Nonthaburi in overall was at the highest level. The mean is arranged in descending order as follows: physical characteristics, intelligence and ability, personality, task–related characteristics, social characteristics, and social background, respectively 2. The efficiency teacher’s performance in the schools under the Secondary Educational Service Area Office Nonthaburi in overall was at the highest level. The mean is arranged in descending order as follows: teacher duties performance, relationships with parents and the community, and learning management 3. The characteristics of professional administrator affecting the efficiency teacher’s performance in the schools under the Secondary Educational Service Area Office Nonthaburi in overall was statistical significance at 0.05 level. The priorities are: social characteristics, task–related characteristics and physical characteristics. There was a multiple correlation coefficient (Multiple R) of .719, in which the variables discussed the variance of the efficiency teacher’s performance in the schools under the Secondary Educational Service Area Office Nonthaburi Province 51.7 percent (R2 = .517), which can be written as a regression analysis equation as follows. Forecast equations in raw score form y ̂tot = 1.09 + .182 (X1) + .280 (X5) + .306 (X6) (R2 = .517) Forecast equations in standard score form z ̂y = .176 (zx1) + .297 (zx5) + .344 (zx6) (R2 = .517)